Investigation into heavy metals in storm wastewater from Vilnius Žirmūnai district and pollutantits spread model in Neris river - Vasarevičius, Saulius; Mineikaitė, Asta; Vaitiekūnas, Petras (Journal of Environmental Engineering and Landscape Management, 2010)
The paper discusses investigation into uncleaned storm wastewater pollution with heavy metals in Vilnius Žirmūnai district. The goal is to determine the dependency of storm wastewater pollution with heavy metals on transport intensity. After determining this dependency, sweeps from street points is experimentally studied with the most intensive transport flows. As the street sweeps together with storm wastewater are both outflow from streets and through outflow pipes directly to the Neris, heavy metals in the outflow pipe sludge are also studied for each pool. The following heavy metals have been experimentally studied: Pb, Mn, Cr, Zn, Cu, Ni. The flame atomic absorption spectrometry method was used. The process of analysis is explained in short and its results are provided. A mathematical model by Phoenics 3.5 version program showing the distribution of heavy metals in the Neris river stream is made on the basis of the results received.Reikšminiai žodžiai: lietaus nuotekos, išleistuvai, sunkieji metalai, gatvių sąšlavos, Neries upė, Žirmūnai, teršalų sklaida.Sunkiųjų metalų kiekių tyrimas lietaus nuotekų išleistuvuose nuo Vilniaus Žirmūnų rajono ir jų sklaidos modelis upėjeSantrauka. Nagrinėjama nevalomų lietaus nuotekų tarša sunkiaisiais metalais Vilniaus Žirmūnų rajone. Siekiant nustatyti ryši tarp lietaus nuotekų užterštumo sunkiaisiais metalais nuo transporto eksperimentiškai tiriamos sąšlavos nuo gatvių, kuriuos su lietumi išplaunamos i upe. Taip pat tiriami sunkieji metalai iš lietaus ištekamųjų vamzdžių į Nerį. Eksperimentiškai nagrinėjami šie sunkieji metalai: Pb, Mn, Cr, Zn, Cu, Ni. Tam panaudotas liepsnos absorbcijos spektrometrinis metodas. Trumpai aptariamas analizės procesas ir pateikiami tyrimų rezultatai. Remiantis gautais rezultatais sudaromas matematinis teršalų sklaidos modelis Neries upės tėkmėje taikant Phoenics 3.5 programą.Исследование количества тяжелых металлов в дождевых стоках района Жирмунай города Вильнюса и модель их распределения в рекеРезюме. Исследуется загрязнение неочищаемых дождевых стоков тяжелыми металлами в районе Жирмунай г. Вильнюса. Для определения степени загрязнения дождевых стоков тяжелыми металлами от транспорта экспериментально исследовался мусор с улиц, вымываемый с дождем в реку. Также исследовались тяжелые металлы в дождевых стоках, попадающих в реку Нерис. Экспериментально с применением абсорбционно-спектрометрического метода исследовались тяжелые металлы Pb, Mn, Cr, Zn, Cu, Ni. Рассмотрен процесс анализа и результаты исследований. На основе полученных результатов составлена математическая модель распределения загрязняющих веществ в течении реки.Ключевые слова: дождевые стоки, тяжелые металлы, очистка, река, Жирмунай, распределение загрязняющих веществ.First Publish Online: 10 Feb 2011